Filsafat Pendidikan Islam di Era Digital: Membangun Karakter Religius di Tengah Arus Teknologi: Penelitian - Burhanuddin; Bintang Arif Samudra; Mat Amin; Salminawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the role of Islamic educational philosophy in shaping the religious character of students in the digital era that is full of information technology flows. The main focus of this study is how the basic values ​​of Islamic education, such as monotheism, morality, and spirituality, can be implemented effectively in a modern learning environment dominated by technology. The method used is a qualitative method with a literature study approach, through analysis of classical and contemporary Islamic educational philosophy literature, as well as a study of digital-based education phenomena. The results of the study show that Islamic educational philosophy has a strong foundation in shaping a complete and religious personality, even amidst the challenges of the digital era. The integration of Islamic ethical principles and the use of educational technology is the key to creating a generation that is intellectually intelligent and spiritually strong. However, the main challenge lies in the dominance of secular digital content and the weak control of parents and educators in guiding the use of technology wisely. This study is expected to provide a new direction in the formulation of Islamic curriculum and learning methods that are adaptive to the development of the times without losing the spirit of Islam